The impact of economic growth on urbanization, transmigration, employment opportunities, and urban population in the context of middle-income trap (a case study of Padang, West Sumatra) - Yusuf Kristiadi; Herdis Herdiansyah (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Introduction: Padang, West Sumatra is especially concerned in this article where the causal effects between the economic growth, urbanization, transmigration, employment, Middle-Income Trap are explored. This study enhances the understanding of interdependencies of factors affecting economic growth, employment opportunities and urban population in Padang, and offers practical guidelines in managing the issues encountered by the city. Methods: In conducting this study, quantitative research method known as System Dynamics method is employed and in addition to this a literature study as a qualitative method is also conducted to have an overall understanding about the system dynamics of the various factors that affect the economic growth, employment opportunities and the population in Padang city. Findings: The findings also indicate that economic growth enhances the welfare of the of the urban residents while it degrades the employment probability. Although there are great gains on the economic aspect, the unemployment rate is not remarkable which means that it continues to be high. This can be attributed to the middle income trap which shows that the Padang economic growth does not translate to improved employment rate. Conclusion: For Padang to avoid falling into middle income trap as well as employment problem the government should take the challenges of job creation and better quality jobs in the formal sector, improve the quality of education and training and promote innovation and creativity. Moreover, the government is required the key causes which led to unemployment levels like poverty and income inequality, the poverty reduction policies is compulsory on the countryside.